(untitled) (Voice: A Biannual & Bilingual Journal, 2023)
This research paper highlights the importance and rationale of standardization in the Tharu language spoken in Nepal. It has some variants throughout Nepal and is being used on the individual styles of accent and pronunciation. These individual styles of speaking and writing the language have created some confusion and occasional linguistic disputes. This research project aims at mitigating such linguistic controversy. The native speakers of the Tharu language are found to have been pronouncing cerebral and dental sounds haphazardly. It happens so because the language hasn’t been authentically standardized so far although it has had lots of literary activities with quite a good folk literature too. The Tharu language is the fourth largest language of Nepal. It’s the major language of southern Nepal from the east to the west but it doesn’t have any authentic linguistic guidelines. Being centred on these points, the paper advocates for the standardization of the Tharu language with the authorized publication of grammar books, dictionaries, etc. Views of various authors regarding the standardization of language have been presented in this paper that has adopted the qualitative research method. The analysis and discussion have been made primarily based on the secondary sources of data with the conclusion that the Tharu language is in dire need to be standardized for its spread and quality as well.